The Effect of Short Range Correlation on The Nuclear Charge Density Distribution, Elastic and Inelastic Electron Scattering Coulomb Form Factors of 18O Nucleus - K. Hamoudi, Adel; S. Mdekil, Abdullah (Iraqi Journal of Science, 2023)
The effect of short range correlations on the inelastic longitudinal Coulomb formfactors for the lowest four excited 2+ states in 18O is analyzed. This effect (whichdepends on the correlation parameter β) is inserted into the ground state chargedensity distribution through the Jastrow type correlation function. The single particleharmonic oscillator wave function is used with an oscillator size parameter b. Theparameters β and b are, considered as free parameters, adjusted for each excited stateseparately so as to reproduce the experimental root mean square charge radius of18O. The model space of 18O does not contribute to the transition charge density. Asa result, the inelastic Coulomb form factor of 18O comes absolutely from the corepolarization transition charge density. According to the collective modes of nuclei,the core polarization transition charge density is assumed to have the form of Tassieshape. It is found that the introduction of the effect of short range correlations isnecessary for obtaining a remarkable modification in the calculated inelasticlongitudinal Coulomb form factors and considered as an essential for explanation thedata amazingly throughout the whole range of considered momentum transfer.PACS: 25.30.Dh; 21.60.Cs; 27.20.+n